Karakteristik Sosio-Budaya, Pergeseran dan Pola Adaptasi Kriya Gerabah Pagelaran Malang - Iriaji, Iriaji; Rohidi, Tjetjep Rohendi; Florentinus, Totok Sumaryanto; Kartika, Dharsono Sony (citeus, 2019)
This research is aimed to study the phenomena of the socio-cultural characteristics, the shift of shape variety, techniques of production, function, as well as the adaptation pattern of the pottery makers of Pagelaran. The study is done holistically and in depth by using qualitative approach through the design of phenomenology. The factual data is gained through in depth interviews, observation and study of documentation with the researchers acting as the key instrument. The validity of the data is maintained by using the source triangulation technique, triangulation of methods, and triangulation of theory. The data are analyzed through the process of reduction, presentation, verification, and paradigmatic theory analysis by using the perspective of the theory of socio-culture, aesthetic of crafting art, and adaptation. This research resulted some points, first is the characteristics of the community of pottery craft of Pagelaran that is heavily holding the Malangan local culture, yet the Javanese culture still heavily attached especially in the behavior of mutual cooperation and the practice of traditional ceremony. Second, the presence of shifting of pottery shaping, technique, and the function of the pottery craft of Pagelaran from the point that they are only making the traditional pottery products into making the creative and innovated pottery products. Third is the findings of two adaptation patterns that is done by the pottery craft community of Pagelaran, that is the functional adaptation pattern through the concept of revitalization and the adaptation pattern processual through the concept of reinterpretation.